2022
DOI: 10.1038/s41598-022-12606-6
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of DUI in the Mediterranean alien species Brachidontes pharaonis (P. Fisher, 1870) despite mitochondrial heteroplasmy

Abstract: Two genetically different mitochondrial haplogroups of Brachidontes pharaonis (p-distance 6.8%) have been identified in the Mediterranean Sea. This hinted at a possible presence of doubly uniparental inheritance in this species. To ascertain this possibility, we sequenced two complete mitogenomes of Brachidontes pharaonis mussels and performed a qPCR analysis to measure the relative mitogenome copy numbers of both mtDNAs. Despite the presence of two very similar regions composed entirely of repetitive sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…1 ). Additional ORFs and extensions of cytochrome c oxidase subunits have been speculated to function as a tagging mechanism allowing cells to distinguish M-type mitochondria from those of female-type 19 , 60 63 , but here we see extensions completely lacking homology to each other which seems to reduce the strength of this argument. The M-type mitogenomes of Macoma balthica and Scrobicularia plana , beside putative ORFs, contain extremely long open reading frame for cox2 gene 43 that recently was shown to have an intronic sequence 42 but might also code for unusually long protein 64 .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…1 ). Additional ORFs and extensions of cytochrome c oxidase subunits have been speculated to function as a tagging mechanism allowing cells to distinguish M-type mitochondria from those of female-type 19 , 60 63 , but here we see extensions completely lacking homology to each other which seems to reduce the strength of this argument. The M-type mitogenomes of Macoma balthica and Scrobicularia plana , beside putative ORFs, contain extremely long open reading frame for cox2 gene 43 that recently was shown to have an intronic sequence 42 but might also code for unusually long protein 64 .…”
Section: Discussioncontrasting
confidence: 58%
“…For this reason, females are homoplasmic, while males are heteroplasmic, possessing two different mitogenomes inherited from both parents. In detail the whole DUI phenomenon becomes a bit more intricate due to reports of exceptions form the general rule, such as the leakage of M-type mitogenomes to somatic tissues 7 10 , the identification of M-type mtDNA in female individuals 11 13 , masculinization 14 16 , recombination 17 , 18 , or even instances of heteroplasmy not correlated with sex 19 . Mitochondrial M and F lineages evolve at different rates.…”
Section: Introductionmentioning
confidence: 99%
“…Non-obvious small taxa such as Modiolarca subpicta , Cantraine, 1835 [ 10 ], and the taxa Mytilisepta virgata Wiegmann, 1837, have attracted less scientific attention. Many bivalve species exhibit a distinctive pattern of mitochondrial inheritance known as doubly uniparental inheritance (DUI) [ 11 ]. At present, no studies have reported whether there is DUI in the mitochondria of M. virgata .…”
Section: Introductionmentioning
confidence: 99%
“…However, all DNA samples were obtained from adductor muscles in this study; 22 of the 171 COI sequences were M-COI, which is not consistent with the canonical DUI pattern in which all COI sequences would be F-COI sequences [20]. There are three possible, non-mutually exclusive explanations for this finding: (1) the introgression of specific male-lineage genes, such as M-COI and M-12S, in M. strigata, which results in an unusual DUI pattern [23]; (2) mitochondrial heteroplasmy in which both mitogenomes are present in many tissues of both sexes [39]; and (3) variation in the efficacy of the same pairs of primers for amplifying two lineages sequences [40]. In species with unusual DUI patterns, the presence of M-mtDNA in the adductor muscles of female individuals might reflect sperm mitochondria not having been eliminated in the eggs and that it had dispersed randomly in the blastomeres; in male individuals, sperm mitochondria might have broken away, aggregated, and migrated to adjacent adductor muscle cells [41][42][43].…”
Section: Discussionmentioning
confidence: 57%
“…The percentage of nucleotide divergence (p-distance) between the two types of COI sequences varied among species showing a DUI pattern; for example, the pdistance between two types of the COI sequences was 8% in the veneroid Artica islandica [44], 17% in the nuculanoid Ledella sublevis [45], 20.5% to 20.8% in M. strigata [23], 24% in the mytiloid Mytilus edulis [46], and 50% in the unionoid Inversidens japanensis [47]. No DUI pattern has been detected in the Mediterranean alien species Brachidontes pharaonic despite mitochondrial heteroplasmy (p-distance of 8.6%) [39]; this suggests that the DUI pattern might be absent in M. strigata. The 16S sequences were relatively conserved in M. strigata; however, variation in the 16S sequences has been detected in Donax vittatus and other species in which a DUI pattern has been detected, including Mytilus galloprovincialis [48] and Perumytilus purpuratus [49].…”
Section: Discussionmentioning
confidence: 99%